16S rRNA Gene Sequencing Assessment of the Prokaryotic Communities in the Southeast Andaman Sea, Thailand and Potential Environmental Alerts - Khunnalack Khitmoh (Science Faculty of Chiang Mai University, 2019)
The microbial community in an ecosystem can be a guide to its environmental condition. This research utilized culture-independent 16S rRNA gene sequencing to obtain preliminary profiles of marine prokaryote communities at 15 km (PT) and 52 km (TC) offshore of the coastal Andaman Sea, Phang Nga, Thailand. The more inland, PT site, exhibited lower prokaryote biodiversity and metabolic potentials than the TC site further offshore. The presence of a relatively high level of nitrite oxidizing Nitrosospira at PT (6.34%) raises an alert for potential coastal nitrogen pollution. The presence of selenium-reducing Sedimenticola at TC (8.35%) suggested an unusual presence of selenium that might be caused from underwater seismic activity, as a minimum of four tsunami events have occurred in this area previously. Monitoring these microorganisms may help understand the marine microbial communities around the tsunami-effected area and also the underwater sediment resuspension level. Our sequencing data highlighted the unique hydrography at this oceanographic position comprising freshwater from India and mangrove forest water runoff from Thailand, together with the underwater land-slip. Global ocean comparison indicated bacterial diversity around TC and PT, similar to two other sites off Thailand (Tha Wang, Tham Phang and differing to that from the distant GS012, GS110b and GS049 sites. The potentially abundant microbial metabolic subsystems in TC supported its high biodiversity, whereas the missing metabolic subsystems in PT might require vigilant monitoring of the condition of Thai Andaman coast. Compared with the culture-dependent method, more than 26-fold number of species were recorded. Moreover, many cultured isolates were not the major species in the culture-independent profile. The data supported the significance of the culture-independent approach in obtaining the more comprehensive microbial databases.